Underutilization of epilepsy surgery in ASEAN countries - Thuy Le, Minh-An; Fong, Si Lei; Lim, Kheng Seang; Gunadharma, Suryani; Sejahtera, Desin Pambudi; Visudtibhan, Anannit; Chan, Derrick; Vorachit, Somchit; Chan, Samleng; Ohnmar, -; Chua, Annabell E.; Cabral-Lim, Leonor; et al. (Elsevier, 2019)
Purpose: This survey was performed to determine the availability of epilepsy surgery, and understand the limiting factors to epilepsy surgery in ASEAN countries with total of 640 million population. Method: A cross-sectional survey was completed by national representatives in all ASEAN countries (Brunei, Cambodia, East Timor, Indonesia, Laos, Malaysia, Myanmar, Philippines, Singapore, Thailand, and Vietnam). Results: Overall facilities for initial epilepsy pre-surgical evaluation are available in most countries, but further non-invasive and invasive investigations are limited. Three countries (Brunei, Cambodia, and East Timor) have no epilepsy center, and 2 countries (Laos, Myanmar) have level 2 centers doing tumor surgery only. Level-3 epilepsy centers are available in 6 countries (Indonesia, Malaysia, Philippine, Singapore, Thailand, Vietnam); only 5 countries (Indonesia, Malaysia, Philippine, Singapore, Thailand) has at least one level-4 epilepsy care facility. Indonesia with 261 million population only has one level 3 and another level 4 center. The costs of presurgical evaluation and brain surgery vary within and among the countries. The main barriers towards epilepsy surgery in ASEAN include lack of expertise, funding and facilities. Conclusions: Epilepsy surgery is underutilized in ASEAN with low number of level 3 centers, and limited availability of advanced presurgical evaluation. Lack of expertise, facilities and funding may be the key factors contributing to the underutilization. © 2019 British Epilepsy Association